Increased Migratory and Activation Cell Markers of Peripheral Blood Lymphocytes in an Experimental Model of Nephrotic Syndrome - Wagner de Fátima Pereira; Gustavo Eustáquio Alvim Brito-Melo; Cláudia Martins Carneiro; Dirceu de Sousa Melo; Karine Beatriz Costa; Fábio Lourenço Tadeu Guimarães; Etel Rocha-Vieira; Érica Leandro Marciano Vieira; Ana Cristina Simões e Silva (Hindawi Limited, 2015)
The present study aimed to evaluate the expression of CD80 and CD18 in subpopulations of peripheral blood leukocytes and oxidative kidney damage in rats with nephrotic syndrome (NS) induced by doxorubicin (Dox) in comparison to control animals at different time points. Male adult Wistar rats were submitted to 24-hour urine and blood collection for biochemical and immunological analysis at 7, 14, 21, and 28 days after Dox injection. After euthanasia, the kidneys were removed for histological analysis and the evaluation of oxidative stress. The phenotypic characterization of leukocytes was performed using flow cytometry. Dox-injected animals exhibited increased CD18 expression in cytotoxic T lymphocytes, NK cells, and monocytes and high CD80 expression in monocytes. Kidney oxidative damage was positively correlated with CD80 expression in monocytes and serum levels of creatinine. These results suggest that phagocytic and cytotoxic cells are preferentially recruited to the tissue injury site, which may contribute to kidney dysfunction in this animal model of NS. The blockade of integrin and costimulatory molecules may provide new therapeutic opportunities for NS.